When good turns to bad and alien predators appear: The dynamics of biodiversity change in boreal waterbird communities - Pöysä, Hannu; Lammi, Esa; Pöysä, Silvo; Väänänen, Veli-Matti (Elsevier BV, 2023)
Temporal patterns of biodiversity are often difficult to interpret because of our limited understanding of how communities vary through time and how processes drive this variation. A further challenge with dynamic systems is choosing an appropriate baseline against which biodiversity change is judged. We used abundance time series of breeding waterbirds in eutrophic lakes in Finland for 1946–2022 to study the dynamics of biodiversity change in local communities and the relative role of two presumed main drivers, i.e. eutrophication and alien predators, in contributing to historical and recent trends in local abundances and biodiversity. We set the cut-off for the historical and recent study periods in the mid-1980 s, because the systematic monitoring of breeding waterbirds in Finland started in 1986 and recent analyses of biodiversity change and population trends in European boreal waterbird communities are mainly based on time series and data gathered since 1986. Both species richness and the total abundance of waterbirds in local communities showed contrasting trends between historical (gathered before the mid-1980 s) and current (gathered after the mid-1980 s) community time series, with the current time series indicating a decline and the historical time series indicating an increase. The abundances of habitat specialists (species preferring eutrophic lakes) and habitat generalists (species using both eutrophic and oligotrophic lakes) showed a corresponding difference between the current and historical time series. The local extinction rates were higher among habitat specialists than among habitat generalists. The trend indices for wetland-nesting species (highly vulnerable to predation by two alien species (the raccoon dog, Nyctereutes procyonoides, and American mink, Neovison vison) in terms of nest site) abundances were more negative than the trend indices of species nesting further away from waterbodies (less vulnerable to predation by two alien species). In addition, bottom-feeding species (presumably more sensitive to negative impacts of eutrophication) did not show more negative population trends than surface-feeding species (presumably less sensitive to negative impacts of eutrophication). Regardless of equal sensitivity to negative impacts of eutrophication, two species highly vulnerable to two alien predators showed more negative population trends than a less vulnerable species. The results suggest that increased predation has been an important driver of the population and biodiversity declines in the studied waterbird communities. The mid-1980 s may not provide an ecologically appropriate baseline against which changes in the populations and biodiversity of boreal waterbird communities are judged.
Keywords: Alien predators; Biodiversity change; Boreal waterbird communities; Eutrophication; Local extinction; Temporal baseline